2019
DOI: 10.1093/ajcn/nqz042
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome–targeted therapies in nonalcoholic fatty liver disease: a systematic review, meta-analysis, and meta-regression

Abstract: Background Preclinical evidence suggests that modulation of the gut microbiome could represent a new therapeutic target in nonalcoholic fatty liver disease (NAFLD). Objectives The aim of this study was to evaluate the most current evidence for liver-specific and metabolic effects of microbiome-targeted therapies (MTTs) in persons with NAFLD. Methods We search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 49 publications
1
114
0
4
Order By: Relevance
“…Numerous randomized controlled trials (RCTs) in humans across a range of populations, from healthy individuals to those with acute and chronic diseases, have been conducted to examine the health benefits of putative synbiotics. Many trials have been conducted in adults with metabolic diseases, including overweight and obesity 21 , 22 , type 2 diabetes mellitus 23 , 24 and non-alcoholic fatty liver disease 25 , 26 . Other outcomes, such as irritable bowel syndrome 27 , surgical infections 28 , 29 , chronic kidney disease 30 , 31 and atopic dermatitis 32 , have also been investigated.…”
Section: Current Levels Of Evidencementioning
confidence: 99%
“…Numerous randomized controlled trials (RCTs) in humans across a range of populations, from healthy individuals to those with acute and chronic diseases, have been conducted to examine the health benefits of putative synbiotics. Many trials have been conducted in adults with metabolic diseases, including overweight and obesity 21 , 22 , type 2 diabetes mellitus 23 , 24 and non-alcoholic fatty liver disease 25 , 26 . Other outcomes, such as irritable bowel syndrome 27 , surgical infections 28 , 29 , chronic kidney disease 30 , 31 and atopic dermatitis 32 , have also been investigated.…”
Section: Current Levels Of Evidencementioning
confidence: 99%
“…These mixed results also occurred with other serum markers including Gamma-glutamyl transferase (GGT), alkaline phosphatase (ALP), total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), fasting serum glucose (FBS) and inflammatory markers [69,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113]. Given the pattern of mixed results, Table 2 summarizes the most recently published meta-analyses of RCTs with probiotic/synbiotic treatment for NAFLD/NASH populations [114,115,116,117,118].…”
Section: Clinical Application Of Probiotics and Synbiotics In Naflmentioning
confidence: 99%
“…All of the meta-analyses listed indicated that microbial therapies are associated with a significant improvement in ALT and AST [114,115,116,117,118]. Regarding the other serum markers, Liu et al included 15 probiotics and synbiotics RCTs involving 782 patients with NAFLD up to April 2018.…”
Section: Clinical Application Of Probiotics and Synbiotics In Naflmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of Bacteroides has been described as markedly higher in patients with liver fibrosis compared with healthy controls, which influences NAFLD progression (94). Furthermore, probiotic administration has been associated with improved levels of liver markers of hepatic inflammation in patients with NAFLD (95). Accordingly, modulation of the gut microbiome presents a new therapeutic target in NAFLD treatment due to the distinct changes in the composition of gut microbiota.…”
Section: Diet and Hepatocyte Protectionmentioning
confidence: 99%